Biomimicry of Fibrous Materials: The Thermal Conductivity and morphology of Man-Made and Natural Fibrous Materials (Journal of Fiber Bioengineering and Informatics, 2018)
With the aim to gain an appreciation of how nature insulates animal bodies with furs, in this exploratory\rstudy we investigated the TC and morphology of natural and synthetic fibrous materials. Specifically, we\rpresent our experimental observations on coyote, wolverine, and synthetic furs, as well as Polyacrylonitrile\r(PAN) nanofibers and knitted fabric. The TC was measured at a temperature range of \u221210 \u25e6C to 65 \u25e6C.\rThe natural furs consist of fibers with different diameters and cuticular scale patterns. They form coreshell\rfibers with complex cellular structures in the core. The natural furs have lower TC compared to\rthat of the synthetic fibrous structures. The coyote furs have the lowest TC value of \u223c 0.046 W/mK\rat \u221210 \u25e6C. While the TC of all of the samples decreased with temperature, the TC of the natural furs\rdecreased at a higher rate and showed a different behavior with temperature, compared to the synthetic\rfibrous materials.
Keywords: Thermal Conductivity; Natural Fur; HotDisc Method; Heat Transfer; Fibrous Materials